1995
DOI: 10.2307/1939361
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Plasticity in the Shell of the Queen Conch Strombus Gigas

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Ecological Society of America is collaborating with JSTOR to digitize, preserve and extend access to Ecology.Abstract. To evaluate the developmental plasticity of shell morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 42 publications
1
19
0
1
Order By: Relevance
“…Soft-bottom taxa are mostly absent (but see Martín-Mora et al, 1995 andDelgado et al, 2002 for examples of a species found on both rocky and softbottom substrates), as are studies involving predators that use methods other than shell breakage (but see Bourdeau, 2009 for exceptions). It is possible that gastropods living in softsediment habitats or those preyed on mainly by slow-moving shellentry predators (for example, seastars) may rely chiefly on plastic avoidance and/or escape behaviour as their antipredator defense, rather than plastic morphological defenses.…”
Section: Environmental Variability Of Marine Versus Freshwater Enviromentioning
confidence: 99%
See 1 more Smart Citation
“…Soft-bottom taxa are mostly absent (but see Martín-Mora et al, 1995 andDelgado et al, 2002 for examples of a species found on both rocky and softbottom substrates), as are studies involving predators that use methods other than shell breakage (but see Bourdeau, 2009 for exceptions). It is possible that gastropods living in softsediment habitats or those preyed on mainly by slow-moving shellentry predators (for example, seastars) may rely chiefly on plastic avoidance and/or escape behaviour as their antipredator defense, rather than plastic morphological defenses.…”
Section: Environmental Variability Of Marine Versus Freshwater Enviromentioning
confidence: 99%
“…We are aware of only one tropical species in which shell plasticity has been demonstrated. The queen conch (Strombus gigas) shows marked developmental plasticity in shell shape (Martín-Mora et al, 1995) and predator-induced plasticity in behaviour, growth and shell thickness (Delgado et al, 2002). We need many more studies on tropical marine and freshwater gastropods, as it would be interesting to know whether shell plasticity is a general phenomenon in tropical gastropods and to test whether patterns of variation in shell plasticity in temperate and tropical aquatic snails reflect differences in environmental variation between temperate and tropical zones.…”
Section: Biogeographic Patterns Of Phenotypic Plasticitymentioning
confidence: 99%
“…Estimated life spans for the queen conch vary between six (Berg 1976) and 26 years (Coulston et al 1989). In particular, local habitat characteristics, food availability and temperature each exert a strong control on longevity and growth rate (Alcolado 1976;Martín-Mora et al 1995;Stoner et al 1996). Shell morphology and size-at-age may vary greatly among different localities (e.g., slim shell = fast growth; short, bulky shell = slow growth; Martín-Mora et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The number of dactylopores associated with each gastropore also was recorded. Variable numbers of indiv idual gastropores (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) and dactylopores (27-129) were measured fro m each grid. Total nu mber o f grids measured was determined by the surface area of the hydrozoan present on each thin section.…”
Section: Morphometric Anal Ysismentioning
confidence: 99%
“…Hence, a given species may exh ibit different phenotypes depending on the environ ment. Plasticity has been described in many marine taxa including corals [8][9], sponges [10], fish [11], barnacles [12], and mo llusks [13]. The presence and range of taxa shown to exh ibit phenotypic plasticity must be taken into consideration when applying morphological characters to define species.…”
Section: Introductionmentioning
confidence: 99%